Examining the environmental characteristics of drug dealing locations - Barnum, Jeremy D. (Crime & delinquency, 2017)
Illicit drug dealers who operate in open-air markets must access customers in the face of risks posed by law enforcement, customers, and competitors. However, researchers purport that the environmental characteristics of certain locations may allow dealers to balance these competing demands. This research utilizes risk terrain modeling to identify the environmental characteristics of drug dealing locations in Chicago, Illinois, and compares these characteristics across different types of drugs. Results show that a number of place features increase the risk of drug dealing. Although many of these features are common to locations for all types of drug dealing, there are some variations. The findings provide insight into the environmental context of drug market locations, which has implications for researchers and practitioners.